Osmotic Indices and Thromboplastic Activity of Erythrocytes After Freeze-Thawing in Combined Media - Ramazanov, Viktor V.; Volovelskaya, Elizaveta L.; Bondarenko, Valeriy A. (Problems of Cryobiology and Cryomedicine, 2016)
Here we studied the osmotic indices of human erythrocytes, frozen in the media with polymers (dextran, polyethylene glycol 1500), in combined media with polymer and penetrating cryoprotectant (1,2-propanediol), as well as their effect on blood plasma clotting time. During erythrocyte freezing in the media with polymers there were demonstrated their disordered osmotic characteristics, in this case they were spherocyte-shaped and spheroechinocyte-shaped if supplementing the medium with albumin. The erythrocytes, which survived after freezing accelerated plasma clotting in a greater extent as compared to the intact cells. Those frozen in combined media were slightly different by osmotic characteristics from the intact cells, being represented by sphero-echinocytes, but discocytes and stomatocytes under albumin effect. The erythrocytes survived freeze-thawing accelerated plasma clotting, like those, frozen in the media with polymers. Our findings have suggested the erythrocyte freezing in the media with polymers to cause the elimination of asymmetric distribution of phosphatidylserine molecules, transiting onto an outer surface of cell membranes, thereby causing spherocytosis and strengthening a thromboplastic activity of erythrocytes. Erythrocyte freezing in combined media resulted in a partial migration of phosphatidylserine onto an outer side of membrane, and that was sufficient for pronounced strengthening of thromboplastic activity of cells with preserving their osmotic indices. Probl Cryobiol Cryomed 2016; 26(3): 229–237